The use of computers in kindergarten, with or without adult mediation; effects on children's cognitive performance and behavior. - Klein, P. S.; Nir-Gal, O.; Darom, E. (Computers in Human Behavior, 2000)
This study was designed to examine the differential effects of three types of adult interaction with kindergarten children using computers on children's cognitive performance and style of response. The types of adult interaction considered were: (1) mediation: provision of mediation, including behaviors such as focusing, affecting, expanding, encouraging, and regulation of behavior; (2) accompaniment: responding to children's questions; and (3) no assistance: provision of minimal technical assistance. The study sample included 150 kindergarten children, age 5-6 years. Children who engaged in adult-mediated computer activity showed higher levels of performance on a series of cognitive measures and more reflective response styles as compared to the other children. Adults' mediating behaviors found most predictive of children's cognitive performance were expanding, encouraging and regulation of behavior. Findings led to the conclusion that integrating adult mediation in pre-school computer learning environments facilitates informed use of computer technologies and has positive effects on children's performance. Copyright (c) 2000 Elsevier Science Ltd Reprinted by permission of the publisher.